The Effect of Perception of Health Care Service Quality on Patient Satisfaction and Loyalty in Mother and Child Hospital - Victor Pratama; Sri Hartini (Universitas Airlangga, 2020)
This article aims to study the effect of perception of health care service quality on patient satisfaction and loyalty in mother and child hospital. The researcher tried to identify the effect and relationship of each variable. Data collected through an accidental sampling technique among 50 samples in two hospitals in Surabaya, and the data were analyzed using path analysis. The result suggests that the perception of health care service quality does not significantly have a positive effect on patient loyalty. At the same time, there are significant and positive effects on the relationship between the perception of health care service quality and patient satisfaction. Patient satisfaction significantly has a positive effect on patient loyalty. Furthermore, patient satisfaction as a mediator variable mediates the relationship between the perception of health care service quality and patient loyalty. These findings emphasize the importance of these aspects to develop a better mother and child hospital.